Tribology Performance of TiO2-SiO2/PVE Nanolubricant at Various Binary Ratios for the Automotive Air-conditioning System - Safril Safril; Wan Hamzah Azmi; Nurul Nadia Mohd Zawawi; Anwar Ilmar Ramadhan (Automotive Experiences, 2023)
Tribological properties are crucial for air-conditioning system performance. The properties can be improved using nanolubricant. However, the effect of the binary ratio of hybrid nanolubricants on the tribological performance of automotive systems is limited in the literature. Therefore, the present study investigates the tribology performance of TiO2-SiO2 nanolubricants for application in automotive air-conditioning (AAC) systems. The dispersion of TiO2 and SiO2 into PVE lubricant was carried out using a two-step method. Subsequently, the dispersion stability was assessed qualitatively and quantitatively. The samples were characterised by a volume concentration of 0.010%, with variations in the mixture ratio of 20:80, 40:60, 50:50, 60:40, and 80:20. Coefficient of friction (COF) and wear scar diameter (WSD) values were determined using the Koehler Four-ball Tribo Tester and Light Compound Microscopy. The investigation revealed that each sample experienced a reduction in COF, with the 40:60 ratio demonstrating the best ratio with the most significant decrease of 37.09%. At the same time, the COF decreased by 8.34%, 2.12%, 7.37%, and 15.11% for the nanolubricant samples at 20:80, 50:50, 60:40, and 80:20, respectively. The WSD evaluation showed that the 40:60 ratio has the lowest scar diameter of 0.0344 mm and a 37.09% wear rate decrease compared to pure lubricant. Each sample exhibits superior performance when evaluated for tribological characteristics and performance, particularly in the case of nanolubricants with the 40:60 ratio. The TiO2-SiO2/PVE, characterised by a volume concentration of 0.010%, has remarkable efficacy across different binary ratios, making it highly recommended with a 40:60 ratio for lubricating AAC compressor systems.